Applications for a hybrid operating room in thoracic surgery: from multidisciplinary procedures to image-guided video-assisted thoracoscopic surgery - Terra,Ricardo Mingarini (2016)
ABSTRACT The concept of a hybrid operating room represents the union of a high-complexity surgical apparatus with state-of-the-art radiological tools (ultrasound, CT, fluoroscopy, or magnetic resonance imaging), in order to perform highly effective, minimally invasive procedures. Although the use of a hybrid operating room is well established in specialties such as neurosurgery and cardiovascular surgery, it has rarely been explored in thoracic surgery. Our objective was to discuss the possible applications of this technology in thoracic surgery, through the reporting of three cases.